The Influence of digital Literacy on Critical Thinking Skills and Social Studies Learning Outcomes - Yuliana, Yuliana; Ali, Muhamad; Fahrurrozi, Muh. (Sumber Belajar Sejahtera, 2025)
This study investigates the influence of digital literacy on critical thinking skills and social studies learning outcomes among seventh-grade students at SMPN 1 Lenek. Employing a quasi-experimental pretest-posttest control group design, the research involved both experimental and control groups, with the experimental group receiving digital literacy-based interventions. Data were collected using descriptive and inferential analyses, including normality, homogeneity, and hypothesis testing with SPSS software. The results revealed that students in the experimental group achieved higher post-test scores in both critical thinking skills (M = 74.44) and social studies learning outcomes (M = 84.44) compared to the control group (M = 55.56 and M = 59.44, respectively). The findings confirmed that digital literacy significantly improves students’ critical thinking abilities and academic achievement in social studies. This study highlights the importance of integrating digital literacy into classroom instruction to foster higher-order thinking skills and enhance learning outcomes.